"More bang for the buck"? Evidence on the effectiveness of an energy efficiency subsidy - Lara Bartels; Madeline Werthschulte (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
With the aim of limiting global warming, environmental subsidies are a popular public finance instrument to reduce carbon emissions. However, there is little evidence on why subsidies are effective in increasing demand for the goods subsidized. We use a framed field experiment to disentangle and study the relative importance of the price and non-price effects implicit in a subsidy encouraging an energy-efficiency investment. In the experiment, participants decide on purchasing a low-flow showerhead and are either confronted with the introduction of a subsidy or a same-sized price decrease. We find a demand increase of about 3-percent when the price decreases and a significantly larger demand increase of about 9-percent when the subsidy is introduced. An analysis of the underlying channels rules out changes in beliefs and norm perceptions. Positive spill-over effects of the subsidy on other pro-environmental behaviors rather suggest that the non-price effect is explained by a crowding in of intrinsic motivation.
Keywords: C93; D90; H23; Q49; 330; Behavioral public economics; subsidies; spillover; energy efficiency; field experiment